2013
DOI: 10.1161/circep.112.973552
|View full text |Cite
|
Sign up to set email alerts
|

Early Risk of Mortality After Coronary Artery Revascularization in Patients With Left Ventricular Dysfunction and Potential Role of the Wearable Cardioverter Defibrillator

Abstract: Background Implantable cardioverter defibrillator (ICD) implantation for prevention of sudden cardiac death is typically deferred for 90 days after coronary revascularization, but mortality may be highest early after cardiac procedures in patients with ventricular dysfunction. We determined mortality risk in post-revascularization patients with left ventricular ejection fraction (LVEF) ≤35% and compared survival to those discharged with a wearable cardioverter defibrillator (WCD). Methods and Results Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 27 publications
(29 reference statements)
2
71
0
9
Order By: Relevance
“…U pacjentów z wysokim ryzykiem wystąpienia migotania komór można w takiej sytuacji rozważyć zastosowanie kamizelki defibrylującej. Nie ma jednak dowodów z badań randomizowanych potwierdzających skuteczność takiego postępowania [239][240][241].…”
Section: Prewencja Pierwotna Nagłego Zgonu Sercowegounclassified
See 1 more Smart Citation
“…U pacjentów z wysokim ryzykiem wystąpienia migotania komór można w takiej sytuacji rozważyć zastosowanie kamizelki defibrylującej. Nie ma jednak dowodów z badań randomizowanych potwierdzających skuteczność takiego postępowania [239][240][241].…”
Section: Prewencja Pierwotna Nagłego Zgonu Sercowegounclassified
“…chorzy z niską LVEF w pierwszym okresie po AMI i możliwością powrotu funkcji skurczowej lub chorzy oczekujący na przeszczepienie serca), można na pewien czas rozważyć zastosowanie kamizelki defibrylującej (zewnętrzny defibrylator z elektrodami przytwierdzanymi do zakładanej kamizelki), która jest urządze-niem rozpoznającym i przerywającym VT/migotanie komór [239][240][241]260]. Takie urządzenia nie zostały jednak jeszcze przebadane w RCT.…”
Section: Prewencja Pierwotna Nagłego Zgonu Sercowegounclassified
“…Consistent with prior data, however, only 1.3% of those treated with a WCD received appropriate therapy for VT/VF. 54 WCD therapy may also be a reasonable treatment option in appropriate pediatric patients at high risk of SCD. 44,50 Although there is an accumulating series of observational data of WCD use in clinical practice, questions about device efficacy will ultimately require randomized studies.…”
Section: Clinical Experience With Wcdsmentioning
confidence: 99%
“…Given the presumed risk of SCD for these individuals during the waiting period, the WCD may provide a bridge of protection in patients within 90 days of CABG or PCI. 48,52,54 …”
Section: 52mentioning
confidence: 99%
“…Recent studies show a benefit in the early post-myocardial infarction period or after revascularization, with about 1.5% of patients having an appropriate defibrillation. 70 Because it has been shown that as many as 28% of patients can improve their function significantly using appropriate neurohormonal antagonists, 71 it is reasonable to use this strategy as SCD protection while giving the chance for myocardial recovery. A summary of pharmacologic and electrical treatment strategies for SCD prevention in patients with heart failure is listed in Table 3.…”
mentioning
confidence: 99%